Respuesta :
Answer:
196
Step-by-step explanation:
Formula for the nth term
- aₙ = a₁ + (n - 1) d
Taking n = 64
- a₆₄ = 7 + 63(3)
- a₆₄ = 7 + 189
- a₆₄ = 196
Answer:
[tex]a_{64}=196[/tex]
Step-by-step explanation:
Arithmetic sequence
General form of an arithmetic sequence: [tex]a_n=a+(n-1)d[/tex]
where:
- [tex]a_n[/tex] is the nth term
- a is the first term
- d is the common difference between terms
Given:
- [tex]a_1=7[/tex]
- [tex]d=3[/tex]
Substituting these into the equation to find the nth term:
[tex]\implies a_n=7+(n-1)3[/tex]
[tex]\implies a_n=3n+4[/tex]
To find the 64th term, substitute n = 64 into the formula:
[tex]\implies a_{64}=3(64)+4=196[/tex]